2011
DOI: 10.1002/eco.204
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical characterization of small coastal wetlands and forests in the Southern Po plain (Northern Italy)

Abstract: This study is aimed to characterize the shallow groundwater system in the coastal area between the Uniti and Bevano rivers (southern part of the Po plain), where salinization is threatening the coastal ecosystems and posing a major environmental issue for the phreatic water management in the coast. A thin rainwater lens is present at the top of the aquifer in the backshore area and its extent has a seasonal variability. These few centimetres of freshwater represent a thin interface between sea water and the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The phreatic groundwater salinity measurements done by Marconi et al (2011) show that during the summer the freshwater lenses are larger and thicker than in the winter, and this is very likely due to recharge from irrigation water.…”
Section: Difference Between Current and Future Annual Irrigation For mentioning
confidence: 97%
See 1 more Smart Citation
“…The phreatic groundwater salinity measurements done by Marconi et al (2011) show that during the summer the freshwater lenses are larger and thicker than in the winter, and this is very likely due to recharge from irrigation water.…”
Section: Difference Between Current and Future Annual Irrigation For mentioning
confidence: 97%
“…The remaining freshwater consists mostly of lenses floating on top of the salt water ) that may change shape and size over short periods of time (Marconi et al 2011). To better understand the behavior of these freshwater lenses, it is important to know how much freshwater infiltrates into the underlying aquifer.…”
Section: Introductionmentioning
confidence: 99%
“…The threats to coastal ecosystems and water resources associated with salinization of a shallow groundwater water system in the coastal area of the southern plain of the River Po in Italy are highlighted by Marconi et al (2011). Their study focuses on the hydro-chemistry of the predominately brackish groundwater aquifer and a seasonally variable freshwater lens in the upper layers of the aquifer which has been found to represent a thin but important interface between seawater and vulnerable coastal ecosystems.…”
Section: Interactions Across the Interfaces Of Wetland Riparian And mentioning
confidence: 99%
“…These impacts have been attributed to groundwater salinity, shallow water tables, drought, and air pollution [14,15]. The trend in groundwater salinization underneath the coastal pine forest is a process that is progressing in time, as recent studies have demonstrated [16].…”
Section: Introductionmentioning
confidence: 99%